Predicting Angiogenesis by Endothelial Progenitor Cells Relying on In-Vitro Function Assays and VEGFR-2 Expression Levels - Nadin Sabbah; Tal Tamari; Rina Elimelech; Ofri Doppelt; Utai Rudich; Hadar Zigdon-Giladi (Biomolecules, 2019)
Clinical trials have demonstrated the safety and efficacy of autologous endothelial progenitor cell (EPC) therapy in various diseases. Since EPCs’ functions are influenced by genetic, systemic and environmental factors, the therapeutic potential of each individual EPCs is unknown and may affect treatment outcome. Therefore, our aim was to compare EPCs function among healthy donors in order to predict blood vessel formation (angiogenesis) before autologous EPC transplantation. Human EPCs were isolated from the blood of ten volunteers. EPCs proliferation rate, chemoattractant ability, and CXCR4 mRNA levels were different among donors (p < 0.0001, p < 0.01, p < 0.001, respectively). A positive correlation was found between SDF-1, CXCR4, and EPCs proliferation (R = 0.736, p < 0.05 and R = 0.8, p < 0.01, respectively). In-vivo, blood vessels were counted ten days after EPCs transplantation in a subcutaneous mouse model. Mean vessel density was different among donors (p = 0.0001); nevertheless, donors with the lowest vessel densities were higher compared to control (p < 0.05). Finally, using a linear regression model, a mathematical equation was generated to predict blood vessel density relying on: (i) EPCs chemoattractivity, and (ii) VEGFR-2 mRNA levels. Results reveal differences in EPCs functions among healthy individuals, emphasizing the need for a potency assay to pave the way for standardized research and clinical use of human EPCs.